The Contrastive Analysis of the Sound in Vowel and Consonant in English and Batak Language - Lestari Kasih Grasella Nahampun; Herman; Christina Natalina Saragi; Nanda Saputra (Britain International for Academic Research (BIAR-Publisher), 2022)
This Article deals with the Contrastive Analysis of the sound in Vowel and Consonant of English and Batak Language. Since there are so many linguistics elements that exists in both of the language, the researcher try to investigate the Phonetic aspect of the language. This article uses the Descriptive Qualitative research design that elaborating and describing the whole perspective of how the sound of each language elements change when it is pronounced and it is exactly convey the different meaning. The researchers use the Literature review as the techniques of collecting data. The source of the data comes from the Book of Batak Grammar created by J. Echools and H.van der tuuk which is vividly points out the theory of Batak language grammatically. This article adopts the CA or Contrastive Analysis technique in analyzing the data and it is found that there is a similarity and the differences in Batak language sound (Vowel and Consonant) with The English version. It can be seen from the word structure that is change and so does the phonetic transcription that generates the different meaning too.